The Influence Of Liquidity, Leverage and Firm Size on Financial Distress at First Media Tbk. Period 2013-2022 - Maulana, M. Iqbal; Rusnendar, Elan; Musadat, Irfan Achmad (CV ODIS, 2025)
Financial distress can occur in any company, whether small or large. Additionally, the COVID-19 pandemic has caused economic instability in Indonesia, impacting the telecommunications sector and resulting in many companies experiencing financial distress, including PT. First Media Tbk, which has faced a decline in performance for more than five consecutive years. This study aims to determine the extent of the influence of liquidity, leverage, and firm size on the financial distress of PT. First Media Tbk. during the period 2013-2022. The indicators used in this study are the current ratio for liquidity, the debt to asset ratio for leverage, the natural logarithm for firm size, and the Z